Renaissance fun : the machines behind the scenes - Steadman, Philip, 1942- (UCL Press, 2021)
Renaissance Fun explores the technology of Renaissance entertainments in stage machinery and theatrical special effects; in gardens and fountains; and in the automata and self-playing musical instruments that were installed in garden grottoes.